Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Evaluate [tex]\((h)(h + j + 3)\)[/tex] using [tex]\(h = 5\)[/tex] and [tex]\(j = 1\)[/tex].

Sagot :

Sure, let's break down the expression step by step with the given values of \( h \) and \( j \).

We start with the expression:
[tex]\[ (h)(h + j + 3) \][/tex]

First, substitute the given values \( h = 5 \) and \( j = 1 \) into the expression:
[tex]\[ (5)(5 + 1 + 3) \][/tex]

Next, perform the addition inside the parentheses:
[tex]\[ 5 + 1 + 3 = 9 \][/tex]

So now, our expression simplifies to:
[tex]\[ (5)(9) \][/tex]

Finally, multiply 5 by 9:
[tex]\[ 5 \times 9 = 45 \][/tex]

Thus, the value of the expression [tex]\((h)(h + j + 3)\)[/tex] when [tex]\( h = 5 \)[/tex] and [tex]\( j = 1 \)[/tex] is [tex]\( 45 \)[/tex].